Deslocamento do roll-off e proteção esofágica na ablação por radiofrequência hepática e cardíaca : controle da impedância tecidual e temperatura com base no controlador PID bioinspirado - Faria, Rafael Mendes (2024)
Introduction: Radiofrequency Ablation (RFA) is a widely used minimally invasive medical procedure for treating electrophysiological disorders and dysfunctional tissues, such as tumors. The method involves inserting a probe with an electrode into the patient’s body, where the application of radiofrequency generates heat, causing necrosis in the tissue and resolving the disorder. However, RFA carries risks, such as overheating and complications related to temperature distribution in the target tissues and adjacent tissues, which can lead to severe outcomes like esophageal fistula in cardiac RFA. The roll-off phenomenon, characterized by the vaporization of tissue fluids and an increase in impedance, can compromise the success of the procedure, making it less effective and more dangerous. Given the critical nature of these procedures, the search for strategies employing controllers that prevent overheating and efficiently cover more tissue is of utmost importance. These technological advancements would not only improve the safety of the procedure but also increase its efficacy by reducing the risk of complications and providing a more comprehensive solution for treating cardiac and hepatic conditions. Objectives: This research proposes an innovative approach to mitigate the effects of roll-off by developing a bio-inspired dynamic control system. The strategy includes optimizing PID controllers using the Grey Wolf Optimizer (GWO) and Particle Swarm Optimization (PSO) algorithms. The main objective is to enhance cardiac and hepatic RFA by expanding the coagulation area, reducing procedure time, and decreasing tumor recurrence and the development of esophageal fistulas. Methodology: The research was structured into three main studies. The first study consisted of a systematic review, conducted following the PRISMA methodology, under the PROSPERO protocol registered under number CRD42022340100. The review was designed to identify gaps in the literature and gather the most current evidence on RFA, which served as the basis for the physiological data used in subsequent simulations. Studies involving liver, heart, or thyroid gland ablation using in vivo, ex vivo, or in silico techniques were considered. The databases searched included Pubmed (n = 958), Scopus (n = 581), Embase (n = 68), Science Direct (n = 21), Web of Science (n = 181), CINAHL Ebsco (n = 125), and IEEE (n = 333), and studies published in the last ten years, in English and Portuguese, were selected. The systematic review selected 29 studies after screening 1078, providing a comprehensive view of the electrical, thermal, and dynamic parameters in RFA procedures. The second study involved developing a PSO-tuned PID controller applied in ex vivo experiments with porcine liver, demonstrating efficacy in controlling tissue impedance during hepatic ablation, preventing roll-off, and ensuring greater precision in the procedure. The third study employed three-dimensional simulations in COMSOL® software to model temperature distribution during cardiac ablation, using a PID controller tuned by the GWO algorithm. This controller successfully regulated temperature, avoiding overheating of adjacent tissues, such as the esophagus, thereby reducing the risk of severe complications. Results: The thesis generated a systematic review that formed the basis for subsequent experiments, identifying best practices and gaps in the literature. In the second study, the PSO-tuned PID controller proved effective in controlling impedance during hepatic ablation, preventing roll-off, and ensuring a larger ablation area. The third study, using GWO to tune the PID in cardiac ablation simulations, showed that the strategy was effective in controlling temperature distribution, especially in protecting against the emergence of esophageal fistulas. Conclusion: The research presented in this thesis not only advances knowledge on the optimization of RFA procedures but also introduces innovative solutions for the precise control of impedance and tissue temperature, critical aspects for the efficacy and safety of this procedure. The integration of computational modeling, PID controller optimization through advanced algorithms like GWO and PSO, along with experimental validation, results in a robust approach. The results promise to significantly expand the coagulation area, reduce procedure time, and minimize tumor recurrence. By avoiding severe complications such as overheating and the roll-off phenomenon, this research provides concrete advances that can be directly applied in cardiac and oncological applications, representing a valuable contribution to the development of safer and more effective approaches to treating complex medical conditions.